The Effectiveness of Duolingo as an English Learning Platform for Students: A Students Feedback - Malinda, Erra; Daulay, Sholihatul Hamidah (Electronic Journal of Education, Social Economics and Technology, 2024)
This research aims to investigate the effectiveness of Duolingo as an English learning platform based on students’ feedback. The study utilized a mixed-method approach with both quantitative and qualitative data collected through online questionnaires. A total of 22 students participated in the study, consisting of individuals who have used Duolingo as their English learning platform. The findings indicate that the majority of students used Duolingo to improve their language skills for work/school, with an overall interest in learning the English language. The majority of students also had the expectation to improve their overall English proficiency and felt that Duolingo has been effective in improving their speaking, listening, reading, and writing skills. The study found that students rated Duolingo as very effective or quite effective in improving their English proficiency, with a high level of confidence in their English proficiency after using Duolingo. Furthermore, the qualitative data showed that Duolingo's effectiveness is attributed to its user-friendly interface, engaging features, and flexibility.